Glycolytic Dysfunction in Granulosa Cells and Its Contribution to Metabolic Dysfunction in Polycystic Ovary Syndrome - Cao Z; Zhou Q; An J; Guo X; Jia X; Qiu Y (Drug Design, Development and Therapy)
Zhenzhen Cao,1,* Qin Zhou,1,* Jie An,1,* Xiaojing Guo,1 XiaoFang Jia,1 Yuena Qiu2 1Department of Gynecology, Kunshan Hospital of Traditional Chinese Medicine, Kunshan, Jiangsu, 215300, People’s Republic of China; 2Department of Reproductive Medicine, The Second Affiliated Hospital of Fujian Medical University, Quanzhou, 362000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuena Qiu, Email cina2544@fjmu.edu.cnAbstract: Polycystic ovary syndrome (PCOS) is a common endocrine-metabolic disorder in women of reproductive age, marked by hyperandrogenism, ovulatory dysfunction, and insulin resistance, accompanied by significant metabolic disturbances, including glycolytic dysfunction, mitochondrial impairment, and increased oxidative stress. In granulosa cells (GCs), disrupted glycolysis impairs follicular development and compromises oocyte quality, exacerbating reproductive and metabolic abnormalities. At the molecular level, dysregulated energy-sensing pathways, such as AMPK and mTOR, reduce glucose uptake, lower ATP generation, and enhance oxidative stress, fueling disease progression. Epigenetic changes and non-coding RNAs further modulate glycolytic enzyme expression, destabilizing metabolic homeostasis within ovarian follicles. Therapeutically, restoring glycolytic balance using agents like metformin, resveratrol, mogroside V, and nicotinamide mononucleotide (NMN) has shown promise in improving glycolysis, insulin sensitivity, and ovarian function in various models. This review synthesizes current evidence on glycolysis’s critical role in PCOS pathophysiology, its influence on follicular energetics and oocyte quality, and highlights metabolic targets for future therapies, offering a foundation for novel mechanism-driven interventions in PCOS management.Keywords: polycystic ovary syndrome, glycolysis, metabolic dysfunction, insulin resistance, granulosa cells, oxidative stress, metabolic therapy